Conversor CA-CC monofásico de estágio integrado, bidirecional, isolado e baseado em conversores intercalados T-type de 3 níveis - Lima, Welton da Silva (2021)
This thesis presents an integrated single-phase bidirectional ac-dc converter based on a dual-active-bridge (DAB) topology. The primary side is based on a multi-state switching cell (MSSC) with a T-type (TNPC) cell, which is composed of two three-level interleaved legs and coupled inductor, while the secondary side is a single-phase full-bridge (FB). Simulation results are presented to evaluate the proposed topology that can be used as a on-board battery charger for electric vehicles (EV) that fits into levels 1 and 2 of the SAE and IEC Standards. The basic converter operating principles and experimental results of a 850 W prototype are presented in order to validate the theoretical analysis. Moreover, a comparative analysis between an isolated ac-dc converter with a neutral point clamped (NPC) converter on the primary side is presented. The control strategy is implemented on the TMS320F28379D DSP. The proposed topology achieves a maximum efficiency of 91.40% at 300 W output power, and 89.40% at rated power. From the experimental results, it can be stated that the converter based on the T-type topology is more efficient than the structure based on the NPC.